MENELISIK PERKAWINAN DI BAWAH UMUR DI KECAMATAN LARANGAN, KABUPATEN BREBES, JAWA TENGAH - Agus Mulyono (Harmoni, 2013)
The aim of this research are knowing the meaning of marriage for the couples of underage marriage; knowing the problems and the effect of social, law and economic and reproductive health for the marriage couple; revealing the things that underlie the society to do this kind of marriage; knowing the public response, ulama and government upon the occurrence of underage marriage and revealing the efforts being made to tackle the underage marriage in the community . This research was held in July-August 2012. This research was conducted using a qualitative approach to data collection, interviews, observation, and study documents . The results shows that the cause of this marriage are pregnant before marriage, the families urge who want have son or daughter in law, and also because of family economic problems . Mostly, the people still think that if the girls have aged over 18 years, she will be said to be an old maid , lack of socialization Marriage Act so that people do not understand the rules .